Islamic Education and Concept of Gender Using a Culture Approach in Minangkabau - Azzahra, Ana; Shadrina, Shadrina; Wardana, Ghufron Akbari; Yandrizal, Debi; Hasim, Rudi (Khalifa: Journal of Islamic Education, 2021)
This study aims to analyze Islamic education and the concept of gender with a cultural approach in Minangkabau. This study uses a qualitative method with content analysis, all data are taken from theories, opinions of experts, and results of previous research on related issues. The data that has been collected is analyzed through identification, categorization, and conclusions. Overall this article will discuss three topics, i) gender and matrilineal culture in Minangkabau, ii) Islamic education in Minangkabau and iii) relevance of culture, gender, and Islamic education in Minangkabau. The implication of this article is that gender with cultural perspective in Minangkabau has regulated the functions and roles of men and women according to their portions, therefore the concept of gender in Minangkabau culture can be used to the platform in understanding functions and roles of men and women in Islamic education. The understanding of the concept of gender in Minangkabau culture has been discussed in this article at least can be used as initial information and reading material for next researchers to examine this problem in context and different issues.